Play and Learn 3D (PAL3D®) A collaborative Way of Learning Project Management with Minecraft® - Alcelay, Claudia (International Journal of Advanced Corporate Learning (iJAC), 2018)
This is an amazing way of learning about Project Management (PM) and developing managerial skills with a team in "extreme" circumstances. Plan you project in teams, calculate budget and time requirements, introduce this data in our App and play Minecraft® in our server. App and server are connected so the student will always know the impact of his/her performance and will introduce corrective measures if required, with consensus with the team. Teachers can analyze their learning patterns and infer behavioral models.